PARADIGMA PENDIDIKAN AGAMA ISLAM BERWAWASAN MULTIKULTURAL - Silvia, Deny (STAI Hubbulwathan Duri, 2016)
Islam in Indonesia is brought by the traders. It is not brought by soldiers or terrorists. When we learn the history of Islam in Indonesia, the development of Islamic societies through various ways and media, for example, trade and purchase, marriage, and “dakwah”. In terms of education to build Islamic education with multicultural insights, the educators must have high moral integrity by promoting ethical-moral as an integral part of their personality. Then educators also must have a deep understanding and also has a high sensitivity in analyzing issues of religious which is being developed in the community. Then, these educators help students to be aware of the importance of understanding the culture in society especially on religious term.